THE CURRENT CLASSIFICATION AND SPECIFIC FEATURES OF THE ROENTGENOSONOPATHOMORPHOLOGICAL MANIFESTATIONS OF DIFFERENT FORMS OF MASTOPATHIES - S. B. Zapirova; A. M. Berzhanskaya; N. L. Chazova; N. I. Rozhkova (ABV-press, 2014)
The current diagnosis of breast diffuse and nodular dysplasias is based on the use of clinical, non-invasive and invasive X-ray, ultra- sound, radionuclide diagnostic methods and pathomorphological, cytometric, and molecular biological studies. Analysis of the advantages and disadvantages of various techniques has determined the optimal tactics of an examination and indications for surgical treatment of nodular dysplasias caused by various breast diseases.